Improving the Fluorescence Detectability of Polycyclic Aromatic Hydrocarbons for Evaluation of Workplace Environments of Cement Industries Processing Organic Residues - Silva, Renata P.; Masini, Jorge C.; Ribeiro, Marcela G.; Pedreira, Walter P.; Cardoso, Luiza M. N.; Marchi, Mary Rosa Rodrigues de [UNESP] (Taylor & Francis Inc, 2008)
The burning of organic residues and wastes in furnaces of cement industries has been an attractive and lucrative approach to eliminate stocks of these pollutants. There is a potential risk for producing PAH in the workplace of industries burning organic wastes, so that highly sensitive analytical methods are needed for monitoring the air quality of these environments. An official method for determination of PAH is based on liquid chromatography with fluorescence detection at fixed excitation and emission wavelengths. We demonstrate that a suitable choice of these wavelengths, which are changed during the chromatographic run, significantly improves the detectability of PAH in atmosphere and particulate matter collected in cement industries.
Keywords: HPLC-fluorescence; PAH; residues burning